2017
DOI: 10.22146/jtbb.26744
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Cadmium on Sperm Quality and Fertilization Of Cyprinus carpio L.

Abstract: The objective of the study was to determine the effect of cadmium on sperm quality and fertilization of C. carpio L. Sperm and eggs were collected by abdomen striping from the mature testis and ovary of C. carpio L. This study used one control and four treatment groups of variation on the cadmium concentration (0, 50, 100, 150, and 200 ppm) with eight replications. Sperm motility (mass motility, mass motility duration, and individual motility duration) and viability were measured after three to four seconds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In common carp, only 100 mg/L of Cd 2þ caused a reduction in fertilization rate following fertilization immediately after exposure, whereas 50 mg/L of Cd 2þ did not. 12 In our study, we experienced that 50 mg/L of Cd 2þ did not reduce fertilization even after 120 minutes of exposure. However, 100 mg/L of Cd 2þ has not been examined in the present study; thus, it can be speculated that this concentration can cause the reduction in fertilization rate also in zebrafish.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In common carp, only 100 mg/L of Cd 2þ caused a reduction in fertilization rate following fertilization immediately after exposure, whereas 50 mg/L of Cd 2þ did not. 12 In our study, we experienced that 50 mg/L of Cd 2þ did not reduce fertilization even after 120 minutes of exposure. However, 100 mg/L of Cd 2þ has not been examined in the present study; thus, it can be speculated that this concentration can cause the reduction in fertilization rate also in zebrafish.…”
Section: Discussionmentioning
confidence: 61%
“…The toxic substance can also have an effect on straight line velocity as well as on curvilinear velocity but not to an extent as on PMOT. 15 The effect of heavy metal exposure was examined on the fertilizing capacity of sperm only in 4 fish species: common carp ( Cyprinus carpio ), 12 rainbow trout ( Oncorhynchus mykiss ), 27 -29 topsmelt silverside ( Atherinops affinis ), 30 and African catfish ( Clarias gariepinus ). 31 However, it has been reported that damage can form in spermatozoa (eg, oxidative DNA damages) due to the exposure to toxicants, which effects do not manifest on the motility, morphology, and antioxidant parameters of sperm, yet they can impair embryonic development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, damage to the structure of the fish testicular tubules was caused by Cu exposure (Figure -1). Other studies have found that exposure to pollutants can cause a decrease in GSI [23], change the structure of testicular histology [2], reduce the quality of fish spermatozoa [6], and alter reproductive behavior [24]. Our data show that probiotic supplements can ameliorate the effects of Cu on hematological and GSI parameters (Figures-1 and 2), as well as decrease the absorption of Cu and MDA in the testes (Figures- 3 and 4), and prevent Cu-induced histological damage to fish gonads (Figure -2).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hayati et al . (2017), e.g ., ultra‐acute Cd exposure reduced sperm motility of carp ( Cyprinus carpio L.) at concentrations of 100 mg l −1 or higher. Contrary to the finding of this study, toxic effects of Cd on sperm motility were observed at much lower concentrations in some species.…”
Section: (A) Parameter Df1/df2 F Pmentioning
confidence: 99%